2016
DOI: 10.4238/gmr.15017462
|View full text |Cite
|
Sign up to set email alerts
|

Association between the MTHFR C677T gene polymorphism and essential hypertension in South West Cameroon

Abstract: ABSTRACT. The association of the methylenetetrahydrofolate reductase (MTHFR) C677T gene polymorphism and essential hypertension has been reported but with controversial results in diverse populations in Asia and Europe, thereby suggesting a dependency on ethnicity. The aim of this study was to investigate the association between the MTHFR C677T polymorphism and essential hypertension in a Cameroonian population (Bantu ethnic group) of the South West Region. Analysis of anthropometric and biochemical data in hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
0
16
0
3
Order By: Relevance
“…The polymerase chain reaction–restriction fragment length polymorphism was a genotyping method of choice for most studies (55.3%). Five studies did not provide covariates adjustment, while six reported P values without effect estimates (Table ). Some investigators included multiethnic populations, but participants were stratified by tribes or chiefdoms in only one study …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polymerase chain reaction–restriction fragment length polymorphism was a genotyping method of choice for most studies (55.3%). Five studies did not provide covariates adjustment, while six reported P values without effect estimates (Table ). Some investigators included multiethnic populations, but participants were stratified by tribes or chiefdoms in only one study …”
Section: Resultsmentioning
confidence: 99%
“…For example, AGT ‐T147M was investigated in Algerian and Ghanaian populations, and demonstrated association with both SBP and DBP only in Ghanaians. On the other hand, MTFHR‐ 677C>T was studied in Algerians and Cameroonians with no evidence of association in both populations, while in Moroccans an increased risk of hypertension was found in TT carriers . One polymorphism ( NPCR ‐55C>A) had low minor allele frequency and could not be assessed for its role in hypertension .…”
Section: Resultsmentioning
confidence: 99%
“…Проведенный мета-анализ 27 исследований с участием 5 418 пациентов с эссенциальной АГ и 4 997 лиц с нормальным АД показал наличие взаимосвязи полиморфизма C677T гена MTHFR с заболеванием, особенно в популяциях стран Азии и Европы [16]. По результатам молекулярно-генетических исследований, выполненных у пациентов с АГ из Марокко и Камеруна, также была обнаружена взаимосвязь носительства мутантного ТТ генотипа (C677T) гена MTHFR с развитием заболевания в отличие от генотипа СС; при этом ОШ увеличивалось более чем в 5 раз [17,18]. Широко обсуждается роль изучаемого полиморфизма гена MTHFR в предрасположенности к развитию инсульта, поскольку существуют данные проспективных наблюдений с большим количеством участников.…”
Section: материалы и методыunclassified
“…Согласно последним данным, гипергомоцистеинемия ассоциирована с высоким риском развития АГ и нарушений липидного обмена [26,27]. Наиболее изученная генетическая поломка -мутация гена 5,10-метилентетрагидрофолатредуктазы (MTHFR).…”
Section: Associations Of Candidate Genes Of Ht and Its Risk Factors аunclassified